The influence of service quality and price on consumer satisfaction - Wulansari, Retno; Sulistiani, Sinta; Fauzi, Rini Dianti (Privietlab, 2024)
This research aims to determine the effect of service quality and price on consumer satisfaction with Ayam Geprek Misu Cilenggang, both partially and simultaneously. The method used in the research is an associative quantitative method. The sampling technique used is nonprobability sampling. The sampling method used the Slovin formula, and the sample obtained in this study comprised 92 respondents. Data analysis uses multiple linear regression tests. The research results show that service quality influences consumer satisfaction, price variables influence consumer satisfaction, and service quality and price influence consumer satisfaction at Ayam Geprek Misu Cilenggang.